(untitled) (Research, Society and Development, 2021)
Objective: To identify, through the pertinent literature, the main reasons why the cytological examination still has low demand in Primary Care. Method: The research consists of an Integrative Literature Review, with a qualitative and exploratory approach. Results: Cervical cancer is diagnosed through cytopathological examination. There are several factors that make it difficult to carry out the cytological exam for women to seek the exam regularly, it is necessary to increase the number of places available to facilitate the appointment, as well as carrying out educational activities is extremely important. Conclusion: it is understood that there are several reasons why it is difficult for women to adhere to the Pap smear test, but it is up to the health team to make women aware of its importance, emphasizing the benefits of early detection of cervical cancer for a favorable prognosis and reduction in morbidity and mortality.